Maxillary sinus floor lifting using freeze-dried homologous bone and tibia autologous bone: report on radiographic and histological results - José S. Domínguez-Mejía; Omar Alberto Ramírez-Úsuga; Yonny Alejandro Blandón-López (Universidad de Antioquia, 2017)
Introduction: autologous bone grafts for maxillary sinus floor lifting are widely accepted to reconstruct alveolar ridge defects; however, there are donor sites that have not been fully explored and can be valid alternatives for this type of procedures. The objective of this study was to evaluate the behavior of tibia autologous grafts compared with freeze-dried homologous bone in maxillary sinus floor lifting. Methods: prospective, controlled, randomized study in 11 patients requiring maxillary sinus elevation. Panoramic radiographs were taken in three different moments (pre-surgery, immediately after surgery, and 6 months post-surgery) in the two groups (tibia and freeze-dried), measuring the alveolar ridge height in the posterior maxilla. Bone biopsies were taken in the grafted area 6 months after the procedure. Results: A significant reduction in bone height was found in the group grafted with freeze-dried bone. The group grafted with tibia autologous bone showed greater stability between baseline and 6 months after surgery. The histological sections showed equal conditions between the two groups. Conclusion: tibia bone shows greater stability in the evaluated period in terms of the height obtained in maxillary sinus floor lifting procedures, with clinical and histological characteristics suitable for the placement of implants. This study should be complemented with a larger sample to provide more representative results that can be applied to the general population.